2013
DOI: 10.1038/npp.2013.242
|View full text |Cite
|
Sign up to set email alerts
|

Moonlighting Proteins and Protein–Protein Interactions as Neurotherapeutic Targets in the G Protein-Coupled Receptor Field

Abstract: There is serious interest in understanding the dynamics of the receptor-receptor and receptor-protein interactions in space and time and their integration in GPCR heteroreceptor complexes of the CNS. Moonlighting proteins are special multifunctional proteins because they perform multiple autonomous, often unrelated, functions without partitioning into different protein domains. Moonlighting through receptor oligomerization can be operationally defined as an allosteric receptor-receptor interaction, which leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 194 publications
(251 reference statements)
1
67
0
Order By: Relevance
“…This may involve alterations of receptor protomer recognition (affinity and receptor density) and of the strength of G protein coupling leading to modulatory effects on the receptor protomer signaling cascades and on ion channel activity in the plasma membrane like G protein-coupled inwardly-rectifying potassium channels. A major change brought about by the allosteric receptor-receptor interaction is the change of protomer function through a change in its G protein selectivity from e.g., Gi to Gq or favouring receptor protomer signaling over b-arrestin [100][101][102]. The GPCRs behave as moon-lighting proteins [16] and biased signaling of the GPCR protomers develop [103][104][105].…”
Section: Physiological and Pathological Relevance Of The Allosteric Rmentioning
confidence: 99%
“…This may involve alterations of receptor protomer recognition (affinity and receptor density) and of the strength of G protein coupling leading to modulatory effects on the receptor protomer signaling cascades and on ion channel activity in the plasma membrane like G protein-coupled inwardly-rectifying potassium channels. A major change brought about by the allosteric receptor-receptor interaction is the change of protomer function through a change in its G protein selectivity from e.g., Gi to Gq or favouring receptor protomer signaling over b-arrestin [100][101][102]. The GPCRs behave as moon-lighting proteins [16] and biased signaling of the GPCR protomers develop [103][104][105].…”
Section: Physiological and Pathological Relevance Of The Allosteric Rmentioning
confidence: 99%
“…Homotropic cooperativity is not possible, but allosteric interactions can occur, causing a change in the recognition/decoding processes of the monomers (see upper panel of Figure 3). Thus, it has been shown that depending on which partner is costimulated, the affinity of the D2 receptor for dopamine is either reduced (as in the adenosine A2A-D2 hetero-oligomer; Fuxe et al, 2003Fuxe et al, , 2014 or enhanced (as in the somatostatin SST5-D2 heterooligomer; Rocheville et al, 2000;Agnati et al, 2005b).…”
Section: Iso-receptors As 'Tesserae' Of Rm a Possible Criterion For Rmentioning
confidence: 99%
“…These heteroreceptor complexes are mainly located in the dorsal and ventral striato-pallidal GABA neurons predominantly found in a perisynaptic position outside the postsynaptic membrane of the glutamate synapse operating via volume transmission ( Figure 4) [72,73]. The formation of heteroreceptor complexes may also lead to changes in the allosteric receptor binding sites including their pharmacology [74].…”
Section: Basimglurant and Da Transmissionmentioning
confidence: 99%